Effects of Augmented Reality Exposure Therapy Combined with Cognitive Intervention on Cat Phobia - Yapan, Saadet; Simsek, Nihat Yilmaz; Sutcigil, Levent (SPRINGER INT PUBL AG, 2023)
With the advancement of technology, augmented reality has started to appear as an option in exposure therapies. This article aims to examine the effect of ARET (augmented reality exposure therapy) in combination with cognitive intervention on cat phobia and to evaluate the clients' experiences with ARET. The study was conducted with explanatory sequential design with four participants (all women). The quantitative part of the study was conducted as a single case study. Participants were then interviewed to assess their experiences during and after ARET. Our findings suggest that ARET, used in combination with cognitive intervention, is effective in reducing cat phobia, with the exception of physical contact with a cat. ARET can also be used independently of cognitive intervention. In addition, the advantages and disadvantages of ARET assessed by the clients are also discussed. It should be ensured that ARET is widely used in therapy as an important technique that has an advantage for both clients and therapists.
Keywords: Augmented reality exposure therapy; Cat phobia; Cognitive behavioral therapy; Specific phobia; Single-subject design; IN-VIVO EXPOSURE; VIRTUAL-REALITY; EPIDEMIOLOGY; ACCEPTANCE; ACROPHOBIA; EFFICACY; Psychology; Psychiatry